الإدراك السوسيولوجي لوباء كورونا -بحث في أثر العوامل السوسيولوجية - عريف, عبدالرزاق; ذراع ميدنى, شايب (جامعة الوادي - University of Eloued, 2021)
ملخص: لاشك أن وباء كورونا المستجد واحد من الأوبئة والأمراض التي عرفت انتشارا واسعا وتفشيا رهيبا وسط المجتمعات، والذي اخترق كل الحدود وأزال جميع المسافات. حتى بات يعرف بالعدو الخفي والقاتل الصامت. لذلك كانت غاية هذه الدراسة البحث في عملية الإدراك السوسيولوجي لهذا الوباء، من خلال معرفة: - إلى أي مدى تعتبر العوامل السوسيولوجية (الاجتماعية) عوامل مفسرة ومؤثرة في تفشي هذا الوباء داخل المجتمعات؟ وخلصت الدراسة إلى: -إبراز أهمية العوامل السوسيولوجية في دراسة هذا الوباء بشكل خاص والأوبئة بشكل عام. -ضرورة إشراك التخصصات الاجتماعية في المجالات الطبية. Abstract4 There is no doubt That The new Corona pandemic is one of the pandemics and diseases that have known wide spread and terrible outbreaks among societies, which has penetrated all borders and eliminated all distances. It even became known as the hidden enemy and the silent killer. Therefore, the purpose of This study was to investigate the process of sociological perception of this pandemic, through the knowledge of: To what extent are sociological (social) factors are considered as explaining and influencing in the spread of this pandemic within societies? . This study concluded : Highlighting the importance of sociological factors in studying this pandemic in particular and epidemics in general. The necessity of involving social specialties in the medical fields
مقال
Keywords: الإدراك السوسيولوجي,وباء كورونا,الصحة ة,المجتمع; sociological awareness , Corona pandemic ,society, health